A new experimental model to study shrimp allergy - Valeriano Nunes, Ivanéia; Andrade, Camila Mattos; Guerra, Priscila Valera; Khouri, Mariana Ivo; Galantini, Maria Poliana Leite; da Silva, Robson Amaro Augusto; Faquim-Mauro, Eliana L.; Farias, Leonardo Paiva; Rebouças, Juliana de Souza; Faria, Ana Maria Caetano; Brodskyn, Cláudia Ida (Immunology letters, 2023)
Shrimp is among the most sensitizing food allergens and has been associated with many anaphylaxis reactions. However, there is still a shortage of studies that enable a systematic understanding of this disease and the investigation of new therapeutic approaches. This study aimed to develop a new experimental model of shrimp allergy that could enable the evaluation of new prophylactic treatments. BALB/c mice were subcutaneously sensitized with 100 μg of shrimp proteins of Litopenaeus vannamei adsorbed in 1 mg of aluminum hydroxide on day 0, and a booster (100 µg of shrimp proteins only) on day 14. The oral challenge protocol was based on the addition of 5 mg/ml of shrimp proteins to water from day 21 to day 35. Analysis of shrimp extract content detected at least 4 of the major allergens reported to L. vannamei. In response to the sensitization, allergic mice showed significantly enhanced IL-4 and IL-10 production in restimulated cervical draining lymph node cells. High detection of serum anti-shrimp IgE and IgG1 suggested the development of allergies to shrimp while Passive Cutaneous Anaphylaxis assay revealed an IgE-mediated response. Immunoblotting analysis revealed that Allergic mice developed antibodies to multiple antigens present in the shrimp extract. These observations were supported by the detection of anti-shrimp IgA production in intestinal lavage samples and morphometric intestinal mucosal changes. Therefore, this experimental protocol can be a tool to evaluate prophylactic and therapeutic approaches.